Migration assessment and modelling of residual styrene monomer migrated from polystyrene food contact materials into selected foods - Mat Ariffin, Naziruddin (2020)
Polystyrene food contact materials can be tainted with unreacted residual styrene monomer from the manufacturing process, which later migrate into food when both materials come into contact. Ingestion of styrene is the main concern as it has been classified in group 2B substance (possibly carcinogenic to humans) by International Agency for Research on Cancer IARC (2002). The risk of styrene monomer migration into Southeast Asian cuisines is imminent as the foods are inherently fatty, often prepared by high-heat cooking methods, and commonly serve at hot state. Additionally, data of styrene monomer migration from High Impact Polystyrene (HIPS) into food at prolong storage is rarely modelled. In this study, the effects of fat content, temperature and contact time on styrene monomer migration from General-Purpose Polystyrene (GPPS) into selected Malaysian dishes and beverage were determined. Distilled water, 3% acetic acid, 10% ethanol and palm olein were prepared in addition to the beef soup, curry noodles and pulled tea at four different amounts of fat-contributing ingredients. Two-sided contact migration cell was filled with food simulants and samples at temperature ranging from 40°C to 70°C at different times. Headspace Solid-Phase Micro Extraction (HS-SPME) coupled with Gas Chromatography–Mass Spectrometry (GC-MS) was used to extract, detect and quantify styrene. Styrene levels in palm olein were found as the highest and significantly differed from other food simulants. Styrene levels in food samples with the highest fat content resulted in the highest levels and significantly differed from other formulations. Food simulants and food samples exposed to 70°C for 2hr were found to have the highest styrene levels compared to other conditions of contact. Subsequently, diffusion model based on Fick’s law was used to examine the migration profile of styrene monomer from HIPS pot into yoghurt at different storage periods. Three different brands of plain stirred yoghurt packed in HIPS pot (Y1, Y2, and Y3) were purchased from the established local manufactures. About 18 pots of yoghurt from the same brand and batch were collected during a production month. Migration experiments were conducted at refrigerated condition (±4°C) and samples were instantly analysed during the collection day and every 4 days throughout storage until the product expired (approximately 28 days). Styrene monomer in samples were analysed by performing similar extraction, detection, and quantification method as formerly mentioned. All yoghurts exhibited significant increase in styrene migration levels before it reached the plateau after a certain time period depending on yoghurt. Finally, diffusion coefficient and partition coefficient of the migration process were estimated by means of migration model. Although styrene levels increased substantially throughout storage, its migration into yoghurts was limited as indicated by partition coefficients values (5.181×10-5 to 3.464×10-3). The resulted diffusion coefficients were 2.920×10-18 cm2 s-1 , 1.606×10-18 cm2 s-1, and 1.325×10-18 cm2 s-1 in yoghurt Y1, Y2, and Y3 respectively. Results revealed that the migration of styrene monomer into foods is strongly depended on fat content, temperature and contact time.